Colonialidade e racismo : estratégias de dominação e construção ideológicocultural da ideia de igualdade racial no Brasil - Souza, Terezinha do Nascimento (2016)
This bibliographical research approaches strategical aspects built upon racial relations in Brazil, identifying the main adopted norms used to enslave, dominate exploit and hide the presence of racism. The concept of coloniality, as described by Aníbal Quijano, studied by the Modernity/ Colonialty (M/C) group, helps us understand how the aforementioned dominating elite uses power to strengthen the denial of racism, present since the time of slavery, persisting as a tragic legacy for their descendants. The studies here performed delve into historical facts told in colonial times through modernity, following the trail of exploitation and domination projects until the present days. This domination process is continuous and characterized by appropriation of knowledge, dissemination of ideology, subtraction of the culture of dominated peoples, and amassing of power. We identified the main strategies used by the dominating elite in order to convince society that there is no racism in Brazil. Such intentions are perceived in the idea that Brazil lives a racial democracy. Bibliographical analysis proposed the identification of the observed racial problems. This research also reveals that Brazilian racism, on a daily basis, is ignored.